Avaliação da silagem de grãos úmidos de milho - Jobim, Clóves Cabreira; Reis, Ricardo Andrade; Rodrigues, Luis Roberto Deandrade [UNESP] (My University, 1997)
This work had the objective of evaluating the effects of different percentages of corn (Zea mays L.) cob on the quality of the silage of high-moisture corn grains. The following treatments were studied: percentages of corn cob in the silage (0, 5, 10, 15 and 20%); period of sampling after opening the silos (zero, two, four and six days). The factorial arrangement 5 × 4 was studied according to a completely randomized block design with three replications. The variables studied were not affected by the sampling period. The buffering capacity and the pH were not affected by the cob, while the percent soluble carbohydrates and amoniacal nitrogen increasing until 1.2 and 1.89 unit percent, respectively. Increasing the amount of corn cobs reduced the contents of DM (from 63.9% to 58.6%), CP (from 10.0% to 7.3%), EE (from 4.87% to 3.92%) and the values of DMIVD (from 90.5% to 79.1%) in the silages and increasing the contents of acid detergente fiber (ADF) (from 3.3% to 12.9%) and neutral detergente fiber (NDF) (from 15.16% to 26.1%). The values of brute energy (BE) were not affected (P>0.01) by the cob corn in the silage.

O objetivo deste trabalho foi estudar os efeitos de diferentes porcentagens do sabugo (0, 5, 10 e 20%) na matéria verde (MV) e de quatro períodos de amostragem (zero, dois, quatro e seis dias após a abertura dos silos) sobre a qualidade da silagem de grãos úmidos de milho (Zea mays L.). O arranjo fatorial 5 x 4 foi estudado segundo delineamento inteiramente casualizado, com três repetições. Não houve efeito do período de amostragem sobre as variáveis estudadas. A capacidade-tampão e o pH não foram afetados pela presença do sabugo, e o teor de carboidratos solúveis e N amoniacal aumentaram em até 1,2 e 1,89 unidade percentual, respectivamente, em relação à silagem exclusiva de grãos de milho. O aumento na porcentagem de sabugo reduziu os teores de matéria seca (MS) (de 63,9% para 58,6%), proteína bruta (PB) (de 10,0% para 7,3%), extrato etéreo (EE) (de 4,87% para 3,92%) e os valores da digestibilidade in vitro de matéria seca (DIVMS) (de 90,5% para 79,1%) das silagens, e aumentou os teores da fibra em detergente ácido (FDA) (de 3,3% para 12,9%) e da fibra em detergente neutro (FDN) (de 15,16% para 26,1%). Os valores de energia bruta (EB) não foram afetados (P>0,01) pela presença do sabugo nas silagens.
Evaluation of the silage of high-moisture corn grain
Keywords: DMIVD; Percent of cob; Sampling; Silage grains; Zea mays